2016
DOI: 10.5604/15093492.1220824
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Activity in Patients 10 Years after Hip Replacement Surgery

Abstract: 1. Hip replacement surgery may affect the employment status of patients. 2. The most significant factors influencing cessation of work were a high BMI, living in a rural environment and being female.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 17 publications
0
7
0
1
Order By: Relevance
“…One study was performed in each of Australia, Denmark, Finland, Greece, Italy, and Switzerland; two were performed in each of Canada, France, Japan, Poland, Spain, Sweden, and the Netherlands; five each were performed in Germany and the UK; and seven were performed in the USA. Of these 37 studies, 13 reported RTS [ 29 – 41 ], 22 reported RTW [ 12 , 13 , 42 61 ], and two reported both RTS and RTW [ 28 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…One study was performed in each of Australia, Denmark, Finland, Greece, Italy, and Switzerland; two were performed in each of Canada, France, Japan, Poland, Spain, Sweden, and the Netherlands; five each were performed in Germany and the UK; and seven were performed in the USA. Of these 37 studies, 13 reported RTS [ 29 – 41 ], 22 reported RTW [ 12 , 13 , 42 61 ], and two reported both RTS and RTW [ 28 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of these 37 studies, 13 reported RTS [ 29 – 41 ], 22 reported RTW [ 12 , 13 , 42 61 ], and two reported both RTS and RTW [ 28 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Badany może uzyskać maksymalnie 44 pkt w podskali Ból, 47 pkt w podskali Stan funkcjonalny (chód, codzienna aktywność), 5 pkt w podskali dotyczącej zakresów ruchów w stawie biodrowym i 4 pkt w podskali Deformacje. Sprawność funkcjonalną pacjenta definiuje się jako złą, gdy badany uzyska poniżej 70 pkt, średnią -70-79 pkt, dobrą -80-89 pkt i bardzo dobrą -90-100 pkt [10]. Badanych zważono i zmierzono, wyliczając BMI.…”
Section: Materiał I Metodyunclassified